Efeitos agudos e crônicos dos fármacos paracetamol e propranolol em diferentes biomarcadores de uma espécie de peixe neotropical - Pereira, Beatriz Vieira Ramos (Universidade Federal de São Carlos, 2018)
Aquatic environments contamination has emerged mainly as a consequence of human activities. The presence of xenobiotics in water bodies can drastically affect the ecosystem, as well as to cause deleterious effects to the species. Production, consumption and inappropriate disposal of pharmaceuticals and personal care products (PCPs) have important contribution for such contamination. Despite existing ecotoxicological studies, there is still a lack of data and studies with native species from neotropical regions and the effects of such substances on non-target species. Taking this into consideration, the present study aimed to assess the effects of two pharmaceuticals, paracetamol and propranolol, on the neotropical fish species Phalloceros harpagos, which genus is native to Brazil and Paraguay, through the analysis of biochemical and cellular markers. Paracetamol is an analgesic and antipyretic drug used to treat pain and fever; propranolol is a non-selective β-blocker. The evaluation of toxicological effects of the described drugs was conducted through analysis of biochemical markers that indicate oxidative stress and neurotoxicity, namely catalase (CAT) in the liver, glutathione-s-transferases (GSTs) in the gills and cholinesterases (ChEs) in the head. The test organism was exposed to 5 different concentrations of each drugs under acute (96h) and chronic regimes (28d). For the acute exposure, besides the control (without drug), the concentrations used were 8, 80, 800, 8000, 80000 µg L-1 for paracetamol and 0.1, 1, 10, 100, 1000 µg L-1 for propranolol. For the chronic exposure the concentrations, apart from the control (without drug), were 5, 10, 20, 40, 80 μg L-1 for paracetamol and 0.0625, 0.125, 0.25, 0.5, 1 µg L-1 for propranolol. Acute exposure results showed increased GSTs activity for most concentrations of paracetamol (80, 800, 8000 and 80000 μg L-1) and propranolol (1, 10, 100 and 1000 μg L-1). ChEs had significant increase in activity for acute exposure to paracetamol (80 µg L-1). In the chronic exposure GSTs activity was significantly increased for propranolol (0.25 and 0.5 μg L-1). For the cellular stress biochemical marker, a protein that belongs to the HSP70 family, an increase in the level of immunolabeling was detected after the acute exposure to both paracetamol (8, 80, 800, 8000 e 80000 µg. L-1) and propranolol (1, 10, e 1000 µg L-1). On the other hand, after the chronic exposure a reduction in the level of HSP70 staining was detected after exposure to paracetamol (5, 10, 15, 20, 40, 80 µg L-1) and an increase after the exposure to propranolol (0,0625, 0,125, 0,25 e 0,5 µg L-1). The results obtained in this research indicate an effort of the organism towards recovering its homeostasis after being exposed to the compounds, whether that is through the attempt of getting rid of the xenobiotics and its metabolites (GSTs activity) or even through cellular protection (immunolabiling of HSP70). Thus, under the experimental condition adopted the fish P. harpagos presented alterations on both biochemical and cellular levels, indicating the organism’s primary response after exposure to these pharmaceuticals.
Acute and chronic effects of the pharmaceuticals paracetamol and propranolol in different biomarkers of a neotropical fish species
Keywords: Ecotoxicologia aquática; Phalloceros harpagos; Biomarcadores celulares; Marcadores bioquímicos; Peixes - Efeito da poluição da água; Fishes - Effect of water pollution on; Indicadores biológicos; Indicators (Biology); Aquatic Ecotoxicology; CIENCIAS BIOLOGICAS